The role played by Non-Governmental Organisations in improving water and sanitation in peri-urban areas: a case of ORAP in Umguza. - Ndlovu, Sakhile S. (Midlands State University, 2019)
The study sought to examine the role of ORAP, an operational NGO in improving water and sanitation to the people of Umguza District. The objectives were to explore the water and sanitation situation in the area before the intervention of ORAP and to offer solution on how water and sanitation could be improved in peri-urban areas. Household questionnaires were administered addressing the housing conditions in which the residents lived, water supply and quality, the sanitation situation, refuse or solid disposal and the related diseases. From the targeted 40 households, 83% of the target population are not satisfied with the location of their houses as they are at the peri-urban areas and are mostly affected by the water situation. 17% of the population are satisfied with the housing conditions especially those who can afford drilling boreholes for alternative water source. 27.5% of the population depends on tap water and the majority resort to borehole water (40%) and stored water (32.5%) as alternatives. This is as a result of low water pressure and the poor quality of the water revealing that the residents perceive access to safe water as a challenge. The majority of residents are not satisfied with the sanitation situation as there are blockages and the refuse disposal situation is generally poor. The residents perceive the water related diseases as a threat the dominant being the diarrhoeal diseases. ORAP activities have managed to improve the water and sanitation situation not only in the area of study but throughout the district. Education has improved as the girl children now feel comfortable attending school due to the lavatories made available. It is therefore recommended that the water and sanitation facilities provided should be monitored to maintain the standards.